Actualization Of Indonesian Immigration Policy Related To Human Rights For Refugees In Indonesia - Melina Tri Asmara; M. Alvi Syahrin (Journal of Law and Border Protection, 2019)
Over the past three decades, the nationality of eradicating its Rohingya, a persecuted discrimination against the Rohingya, who are a Muslim minority in Myanmar, has forced thousands of people to seek safety in countries such as Indonesia, Malaysia, Bangladesh and Thailand.. At its peak in 2015 Thailand, Malaysia, and Indonesia initially encouraged refugees who had already reached the coast, but with the work of local and international organizations, Indonesia, Malaysia and Thailand then held a consultation meeting in Putrajaya, Malaysia. During these negotiations, Indonesia and Malaysia finally agreed to provide humanitarian assistance to 7,000 illegal immigrants who were illegal to stay for one year (Ministerial Meeting, 2015). According to data from the Ministry of Foreign Affairs of the Republic of Indonesia, 1,346 refugees from Myanmar and Bangladesh entered Indonesian waters in May 2015. The refugees were resettled in two places in the Aceh region.UNHCR (United Nations High Commissioner for Refugees) appreciates the intention of Indonesia and Malaysia for their willingness to help temporarily accommodate their Rohingya refugees. Based on the change in attitudes of Indonesia and Malaysia, a statement has emerged regarding the welfare and safety of Rohingya refugees for the next few years and how Indonesia can handle problems with third countries for its Rohingya refugees. The lack of solutions related to systematic violence, denial of citizenship for the Rohingya people, and the absence of a cohesive regional framework for migration means that there is a lack of protection space regarding refugees in the protection of their social status. Therefore there is a need for a solution in the future in dealing with several policies that are only temporarily intended as a weak solution related to overcoming the prolonged situation of Rohingya refugees